1990
DOI: 10.1073/pnas.87.3.1223
|View full text |Cite
|
Sign up to set email alerts
|

EPR demonstration of iron-nitrosyl complex formation by cytotoxic activated macrophages.

Abstract: Activated macrophage cytotoxicity is characterized by loss of intracellular iron and inhibition of certain enzymes that have catalytically active nonheme-iron coordinated to sulfur. This phenomenon involves the oxidation of one of the terminal guanidino nitrogen atoms of L-arginine, which results in the production of citrulline and inorganic nitrogen oxides (NO-, NO5, and NO). We report here the results of an electron paramagnetic resonance spectroscopic study performed on cytotoxic activated macrophage (CAM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
221
0
2

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 476 publications
(228 citation statements)
references
References 60 publications
5
221
0
2
Order By: Relevance
“…While NO may be required for tumoricidal function of certain effector cells, excessive NO production can also suppress lymphocyte activation. It has been shown that activated murine macrophages synthesise NO from L-arginine (Stuehr and Marletta, 1985), which may partly mediate the cytotoxic activity of these cells against tumour cells and bacteria (Lancaster and Hibbs, 1990). Mills et al (1992) reported that tumour growth in the peritoneal cavity of mice was associated with a marked decline in the production of NO by intra-tumour macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…While NO may be required for tumoricidal function of certain effector cells, excessive NO production can also suppress lymphocyte activation. It has been shown that activated murine macrophages synthesise NO from L-arginine (Stuehr and Marletta, 1985), which may partly mediate the cytotoxic activity of these cells against tumour cells and bacteria (Lancaster and Hibbs, 1990). Mills et al (1992) reported that tumour growth in the peritoneal cavity of mice was associated with a marked decline in the production of NO by intra-tumour macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…NO has a high affinity for both heme and non-heme iron atoms present in the prosthetic groups of proteins (41). It is the binding of NO to the heme group of soluble guanylate cyclase that activates this enzyme, raising intracellular levels of cGMP in many (3), but not all (42), types of cells.…”
Section: Biochemical Properties Of Nitric Oxidementioning
confidence: 99%
“…released from endothelial cells (the endothelium-derived relaxing factor, EDRF) [3] and the L-arginine-derived cytotoxic effector molecule released from macrophages and other cells is identical with NO [1][2][3][4][5][6][7][8], other investigators have proposed that hydroxylamine [9,10], a nitrosothiol [11] or a mixture of these [10] can also account for the activity of this NO.. This uncertainty derives mainly from the fact that the techniques used to quantify NO in oxygen-containing aqueous solutions are unable to discriminate between NO and labile NO donors.…”
Section: Introductionmentioning
confidence: 99%